EFEK WAKTU MULAI PEMBERIAN RANSUM SETELAH MENETAS DAN IMPLIKASINYA TERHADAP PENAMPILAN AYAM BROILER - Mega Royani (Indonesian Journal of Applied Sciences, 2012)
This study was held to find out the effect of early held feeding times on growth performance, weights of the small intestine andprotease enzyme activity in broiler chickens. The reseach used 192 birds final stock broiler strain Cobb, were randomly placed into twenty four cages and eight birds in every cage unit. The reseach was experimental used Completely Randomized Design (CRD) with six treatments and four replication. The treatment were post-hatch feeding times on 6 hour (R1); 12 hour (R2); 24 hour (R3); 36 hour (R4); 48 hour (R5); dan 60 hour (R6). The result of reseach have shown that post-hatch feeding times until 36 hour can gave are growth performance, weights of the small intestine and protease enzyme activity of broiler with normal result.